Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/v7112909
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis Caused by Toscana Virus Is Associated with Strong Antiviral Response in the CNS and Altered Frequency of Blood Antigen-Presenting Cells

Abstract: Toscana virus (TOSV) is a Phlebotomus-transmitted RNA virus and a frequent cause of human meningitis and meningoencephalitis in Southern Europe during the summer season. While evidence for TOSV-related central nervous system (CNS) cases is increasing, little is known about the host defenses against TOSV. We evaluated innate immune response to TOSV by analyzing frequency and activation of blood antigen-presenting cells (APCs) and cytokine levels in plasma and cerebrospinal fluid (CSF) from patients with TOSV ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…Similarly, our results showed no association of inflammatory markers in the CSF and disease severity. A high intrathecal production of IL-6, IFN-γ, and IL-10 suggests the activation of a selective antiviral and anti-inflammatory response in the CNS of TOSV-infected patients which is in correlation with observations in some other neuroinvasive arboviral infections (flaviviruses) where a strong inflammatory immune response in the CNS was found [23][24][25].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly, our results showed no association of inflammatory markers in the CSF and disease severity. A high intrathecal production of IL-6, IFN-γ, and IL-10 suggests the activation of a selective antiviral and anti-inflammatory response in the CNS of TOSV-infected patients which is in correlation with observations in some other neuroinvasive arboviral infections (flaviviruses) where a strong inflammatory immune response in the CNS was found [23][24][25].…”
Section: Discussionsupporting
confidence: 85%
“…In the other study, no difference was observed in the plasma levels of IL-6, IL-10, TNF-α, IFN-α, and IFN-γ between TOSV-infected patients and controls, however, levels of cytokines in the CSF was significantly higher in TOSV-infected patients. No difference was found in the CSF cytokine production in patients with meningitis and meningoencephalitis [23]. Similarly, our results showed no association of inflammatory markers in the CSF and disease severity.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Japanese encephalitis virus (JEV) infection elicits an elevation of inflammatory cytokine expression through TLR7 signaling to cause neuroinflammation [15]. Meningitis caused by Toscana virus (TOSV) is associated with a strong TLR7-mediated antiviral response in the CNS [16]. Upon EV71 infection, TLR7 usually acts as an inflammatory response modulator in intestinal epithelial cells and immune cells [1720].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of infection is usually good and there is no recurrence of symptoms. The virus, however, has the potential to cause severe aseptic meningitis, meningoencephalitis, and severe infections beyond the currently known geographical range of the virus [32][33][34][35][36][37][38][39][40][41][42][43][44]. Keeping preparedness in focus, it is important to develop tools to study such viruses.…”
Section: Introductionmentioning
confidence: 99%